2011
DOI: 10.1111/j.1600-0463.2011.02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of c‐Met enhances sensitivity to bortezomib in human multiple myeloma U266 cells via inhibiting Akt/mTOR activity

Abstract: The c-Met is a receptor tyrosine kinase that is overexpressed in human myeloma cell lines and promotes the survival and drug resistance of myeloma cells. This study aimed to elucidate the mechanisms by which c-Met contributes to the chemoresistance in myeloma. Stable U266 cell line in which c-Met was effectively knockdown was employed and treated with bortezomib. Cytotoxicity was evaluated by MTT assay. Cell cycle profile and apoptosis were examined by cytometry analysis. The expression of cell cycle related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…It has been previously shown that cMET knockdown by siRNA in U266 multiple myeloma cells increases sensitivity to both bortezomib and doxorubicin (35,36). We thus wondered whether p-cMET inhibition by SU11274 might revert the resistance to bortezomib, melphalan, and doxorubicin in R5 cells: SU11274 in combination with both bortezomib and doxorubicin successfully targeted these cells in a synergistic way [combination index (CI) < 1; isobologram analysis; Fig.…”
Section: Multidrug-resistant Multiple Myeloma Cells Present With a Comentioning
confidence: 99%
“…It has been previously shown that cMET knockdown by siRNA in U266 multiple myeloma cells increases sensitivity to both bortezomib and doxorubicin (35,36). We thus wondered whether p-cMET inhibition by SU11274 might revert the resistance to bortezomib, melphalan, and doxorubicin in R5 cells: SU11274 in combination with both bortezomib and doxorubicin successfully targeted these cells in a synergistic way [combination index (CI) < 1; isobologram analysis; Fig.…”
Section: Multidrug-resistant Multiple Myeloma Cells Present With a Comentioning
confidence: 99%
“…28 Que et al revealed that the down-regulation of MET inhibits the proliferation and invasion of U266 myeloma cells, and increases their chemosensitivity to doxorubicin and bortezomib. [29][30][31] Posttranscriptional gene silencing, a technique that is based on the phenomenon of RNA interference (RNAi) through siRNA, uses the natural process of gene expression dependent on double-stranded RNA. Translation of the mRNA is blocked by the introduction of siRNA with a sequence complementary to the target RNA.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signalling pathway plays an important role in cellular proliferation, motility, apoptosis, drug resistance and survival. 6,15,18,19 Constitutive activation of the PI3K/AKT pathway is considered to be an important molecular event that contributes to the malignant phenotype of the tumour cell in multiple myeloma. 20 The major upstream regulator of AKT is PI3K, which is activated by a variety of transmembrane receptors.…”
Section: Discussionmentioning
confidence: 99%